A systematic review of the molecular simulation of hybrid membranes for performance enhancements and contaminant removals - Yee, Cia Yin; Lim, Lam Ghai; Lock, Serene Sow Mun; Norwahyu, Jusoh; Yiin, Chung Loong; Chin, Bridgid Lai Fui; Chan, Yi Herng; Loy, Adrian Chun Minh; Muhammad, Mubashir (Elsevier, 2022)
Number of research on molecular simulation and design has emerged recently but there is currently a lack of review to present these studies in an organized manner to highlight the advances and feasibility. This paper aims to review the development, structural, physical properties and separation performance of hybrid membranes using molecular simulation approach. The hybrid membranes under review include ionic liquid membrane, mixed matrix membrane, and functionalized hybrid membrane for understanding of the transport mechanism of molecules through the different structures. The understanding of molecular interactions, and alteration of pore sizes and transport channels at atomistic level post incorporation of different components in hybrid membranes posing impact to the selective transport of desired molecules are also covered. Incorporation of molecular simulation of hybrid membrane in related fields such as carbon dioxide (CO2) removal, wastewater treatment, and desalination are also reviewed. Despite the limitations of current molecular simulation methodologies, i.e., not being able to simulate the membrane operation at the actual macroscale in processing plants, it is still able to demonstrate promising results in capturing molecule behaviours of penetrants and membranes at full atomic details with acceptable separation performance accuracy. From the review, it was found that the best performing ionic liquid membrane, mixed matrix membrane and functionalized hybrid membrane can enhance the performance of pristine membrane by 4 folds, 2.9 folds and 3.3 folds, respectively. The future prospects of molecular simulation in hybrid membranes are also presented. This review could provide understanding to the current advancement of molecular simulation approach in hybrid membranes separation. This could also provide a guideline to apply molecular simulation in the related sectors.